Interventions in Ethics - Phillips, D. Z. author. aut Link
XV, 301 p.
Keywords: This collection of essays explores the area of ethics in relation to issues such as the nature of moral endeavour and the request for a justification of moral endeavour. Professor Phillips considers the work of Thomas Nagel and Peter Winch in this book.